Penerapan Teknologi Augmented Reality 3D Sebagai Media Pembelajaran Anak Usia Dini - Fadillah P, Yoga; Handayani, Dwipa; Fathurrozi, Ahmad; Yusuf, Dani; Yasir, Muhammad; Hidayat, Agus (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Traditional learning methods that rely on books and static images often fail to effectively capture children's attention and help them understand the material. This is one of the challenges in increasing learning motivation. To address this issue, an Android-based AR application was developed to teach vowel letters to kindergarten children. By using the fast corner detection algorithm and Unity3D, AR offers a more engaging and effective approach compared to conventional methods. The implementation stages include designing, developing, and testing the application by involving kindergarten children as research subjects to assess the effectiveness of the application. The goal of this PKM is to enhance children's interest in learning, facilitate the understanding of vowel letter concepts, and provide an innovative and interactive learning method. Research results show that AR has the potential to increase children's interest in learning and facilitate the understanding of vowel letter concepts.